2008
DOI: 10.1128/aac.01271-07
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Porphyromonas gingivalis ATCC 33277 to Direct Killing by Antimicrobial Peptides Is Protease Independent

Abstract: Antimicrobial peptides are short, positively charged, amphipathic peptides that possess a wide spectrum of antimicrobial activity and have an important role in the host's innate immunity. Lack of, or dysfunctions in, antimicrobial peptides have been correlated with infectious diseases, including periodontitis. Porphyromonas gingivalis, a gram-negative anaerobe and a major pathogen associated with periodontal diseases, is resistant to antimicrobial peptides of human and nonhuman origin, a feature that likely co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 43 publications
4
37
1
Order By: Relevance
“…Indeed, it has been demonstrated recently that F. nucleatum, which is sensitive to LL-37 (1), enables P. gingivalis growth in saliva (35). "Group protection," where a resistant species in the multispecies dental biofilm protects another species that is sensitive to a host factor, has been suggested previously (2,22,28). Here we suggest a host countermeasure for such phenomena.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Indeed, it has been demonstrated recently that F. nucleatum, which is sensitive to LL-37 (1), enables P. gingivalis growth in saliva (35). "Group protection," where a resistant species in the multispecies dental biofilm protects another species that is sensitive to a host factor, has been suggested previously (2,22,28). Here we suggest a host countermeasure for such phenomena.…”
Section: Discussionmentioning
confidence: 63%
“…Previous experiments using a protease-resistant d enantiomer peptide, a protease-deficient P. gingivalis mutant, and a fluorescently labeled antimicrobial peptide revealed that resistance of P. gingivalis to direct killing by LL-37 is protease independent and results (at least partially) from the low affinity of antimicrobial peptides to P. gingivalis (2). Because proteolytic degradation of LL-37 is nonessential for survival of P. gingivalis, it was suggested that LL-37 proteolysis by P. gingivalis provides neighboring dental plaque species with resistance to LL-37, which in turn benefits P. gingivalis (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Porphyromonas gingivalis is known to hydrolyze AMPs mainly by expressing robust proteolytic activity (27). However, Ouhara et al suggested that Porphyromonas gingivalis resistance to D-enantiomer peptides was independent of its proteolytic capacity (27,28). Thus, the mechanism of bacterial resistance to tachyplesin I requires further research.…”
Section: Discussionmentioning
confidence: 99%